Factor structure and psychometric properties of an adapted HIV stigma tool for measuring disability-related stigma among smallholder farmers in Western Kenya – Findings from a cross-sectional study - Anita Jeyam; Elena Schmidt; Stevens Bechange; Stephen Pye; George Okello; Sheru Muuo; Moses Chege; Emma Jolley (PLoS ONE, 2026)
Background People with disabilities face stigma and discrimination which contribute to barriers and poor outcomes in many areas such as health or employment. There is currently a dearth of tools for measuring disability-related stigma and discrimination in low-and middle-income countries. Aims This study aims to evaluate the construct validity and internal consistency of adapted human immunodeficiency virus (HIV) stigma and discrimination tools for use in the context of disability, among smallholder farmers in Western Kenya. Methods Separate tools were used to measure enacted stigma in the community among people without disabilities, and stigma experienced by people with disabilities. We split the relevant sample in two (N = 3642 for enacted stigma; N = 710 for experienced stigma), using exploratory factor analysis (EFA) on the first half and confirmatory factor analysis (CFA) on the second. Results For enacted stigma, a two factor-structure was identified: negative attitudes towards people with disabilities and positive/supportive attitudes towards people with disabilities. For experienced stigma, the scale was reduced to six items capturing interpersonal stigma, and was unidimensional. CFA model-fit indices were good. McDonald’s omega coefficient indicated good internal consistency for the enacted stigma scale (0.79) and for the experienced stigma scale (0.82). Conclusion The adapted HIV stigma scale showed good properties in terms of construct validity and reliability, for measuring aspects of disability-related stigma. These are promising results to build on to develop locally valid and standardised disability-related stigma and discrimination measurement tools.